2015
DOI: 10.1002/ccd.26257
|View full text |Cite
|
Sign up to set email alerts
|

Fractional flow reserve‐guided paclitaxel‐coated balloon treatment for de novo coronary lesions

Abstract: POBA-FFR-guided PCB treatment is safe and effective for de novo coronary lesions with good anatomical and physiological patency at mid-term follow-up. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 22 publications
0
32
1
Order By: Relevance
“…To the best of our knowledge, this is the first prospective, officially registered study with a dedicated, predefined procedural protocol that investigates the feasibility of elective DCB-only PCI in all-comers and provides a nearly completed 6-month invasive and clinical f/u in all patients. Earlier studies of DCB-only angioplasty of de novo stenoses showed a high conversion rate to stenting (11.9–32.8 %), or investigated a preselected study population [20, 21, 23]. Contrary, bail-out stenting in our study was necessary only in 6 % of cases.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first prospective, officially registered study with a dedicated, predefined procedural protocol that investigates the feasibility of elective DCB-only PCI in all-comers and provides a nearly completed 6-month invasive and clinical f/u in all patients. Earlier studies of DCB-only angioplasty of de novo stenoses showed a high conversion rate to stenting (11.9–32.8 %), or investigated a preselected study population [20, 21, 23]. Contrary, bail-out stenting in our study was necessary only in 6 % of cases.…”
Section: Discussioncontrasting
confidence: 56%
“…3a–c). Our results on positive vessel remodeling are in agreement with previous studies also showing luminal gain at variable f/u times (Scheller 2013: LLL −0.25 to −0.18 mm; Kleber 2015: late lumen increase in 69 % of the lesion, Her 2016: LLL: −0.12 ± 0.30 mm; Shin 2015: LLL 0.05 ± 0.27 mm; Ann 2016: LLL 0.02 ± 0.27 mm) [14, 19, 2123]. Only the Valentine´s II trial showed a LLL of 0.38 ± 0.39 mm at 6–9 months f/u.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we demonstrated that PCB treatment for de novo coronary disease in patients who were unable to receive long-term dual antiplatelet therapy is promising in better tackling PMI than DES implantation. In terms of the safety and efficacy of PCB treatment for de novo coronary lesions, we have already shown that fractional flow reserve guided PCB treatment is safe and effective with good anatomical and physiological patency at follow-up 29. Therefore, we hope that PCB treatment will be used in a broader patient population with de novo coronary disease, thus reducing PMI post-PCI.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, Shin et al (27) presented the similar efficacy and safety of DEB vs. second generation DES in treatment of de novo coronary stenosis even without additional BMS implantation. They emphasized the perfect lesion preparation with predilation to obtain fractional flow reserve (FFR) > 0.85.…”
Section: Discussionmentioning
confidence: 99%